SAT0436 Durability of apremilast response in patients with psoriatic arthritis: long-term (208-week) results from the palace 1 trial. (15th June 2017) - Kavanaugh, A; Gladman, DD; Gomez-Reino, JJ; Hall, S; Lespessailles, E; Mease, PJ; Schett, G; McIlraith, M; Delev, N; Paris, M; Teng, L; Wollenhaupt, J
Abstract : Background: Optimizing treatment choice in psoriatic arthritis (PsA) necessitates an understanding of the long-term effects of therapies across varied manifestations of this complex disease. Data from 4 years of apremilast (APR) treatment in PALACE 1 were used to examine disease control across markers of active inflammation, such as SJC, as well as improvements in patient (pt) functionality, as assessed using the HAQ-DI. Objectives: Evaluate long-term outcomes with APR treatment after ≥1 DMARD or biologic in pts with active PsA. Methods: Pts were randomized (1:1:1) to placebo (PBO), APR 30 mg BID (APR30), or APR 20 mg BID (APR20). The PBO-controlled phase continued to Wk 24, at which time all remaining PBO pts were re-randomized to APR30 or APR20. Double-blind APR treatment continued to Wk 52; pts could continue APR for up to 4 additional years in an open-label extension. Results: 504 pts were randomized and received ≥1 dose of study medication (PBO: n=168; APR30: n=168; APR20: n=168); 86.9% (225/259) of pts entering the third year completed 208 wks of APR treatment; overall, this is 44.6% (225/504) of pts randomized at baseline (BL). At Wk 52, 53.2% of APR30 pts achieved a modified ACR20 response (Table), regardless of when APR was started (BL, Wk 16, or Wk 24). At Wk 208, a sustained response rate was observed in APR30 pts, as shown by an ACR20 response rate of 67.5%. Marked improvements in SJC were seen throughout the study, with a mean percent decrease of −84.2% at Wk 208; TJC reductions were consistent (Table). Functionality is of paramount importance to pts; large improvements were seen in HAQ-DI score, with a mean change of −0.47. Pts also note fatigue as a disease- or treatment-related impairment; a mean improvement of 5.7 was seen in FACIT-F score at Wk 208 (Table), and the pt population reached a mean score of 35.7. In addition, long-term treatment led to the maintenance of the proportions meeting the minimal clinically important difference in HAQ-DI score change, achieving ACR50/ACR70 responses and reaching PASI-75 and PASI-50 responses (Table). No new safety concerns were identified with APR treatment up to 208 wks. During Wks >156 to ≤208, the only adverse event (AE) occurring in ≥5% of APR30-exposed pts was URTI (5.2%); most AEs were mild/moderate in severity. Among APR30-exposed pts, serious AEs occurred in 6.7% of pts in Wks >156 to ≤208, consistent with earlier data. Importantly, few discontinuations due to AEs occurred throughout the long-term treatment period. Conclusions: APR30 demonstrated sustained, clinically meaningful improvements in signs and symptoms of PsA, physical function, and associated psoriasis over 208 wks. APR30 continued to demonstrate a favorable safety profile and was generally well tolerated. Disclosure of Interest: A. Kavanaugh Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, UCB, D. Gladman Grant/research support from: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB, Consultant for: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB, J. Gomez-Reino Grant/research support from: Roche and Schering-Plough, Consultant for: BMS, Pfizer, Roche, Schering-Plough, UCB, S. Hall Consultant for: Boehringer Ingelheim, MSD, Roche, Schering-Plough, Servier, Wyeth, Paid instructor for: Amgen, AstraZeneca, Boehringer Ingelheim, Centocor, GSK, MSD, Pfizer, Sanofi Aventis, Sanofi Pasteur, Schering-Plough, Serono, Wyeth, Speakers bureau: Boehringer Ingelheim, GSK, MSD, Pfizer, Roche, Sanofi Aventis, Schering-Plough, Wyeth, E. Lespessailles Grant/research support from: Amgen, Eli Lilly, Novartis, Servier, Speakers bureau: Amgen, Eli Lilly, Novartis, Servier, P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Genentech, Janssen, Eli Lilly, Pfizer, UCB, G. Schett Grant/research support from: Abbott, Celgene Corporation, Roche, UCB, Consultant for: Abbott, Celgene Corporation, Roche, UCB, M. McIlraith Employee of: Celgene Corporation, N. Delev Employee of: Celgene Corporation, M. Paris Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, J. Wollenhaupt Grant/research support from: Abbott, BMS, MSD, Pfizer, UCB, Consultant for: Abbott, BMS, MSD, Pfizer, UCB